Fictional or Autobiographical Pact? Double Autofiction in Marechal’s Adán Buenosayres (2019)
The particular creative process of self-fiction makes it difficult to delimit any artistic work that belongs to this subgenre. Its double frame, unlike autobiography, allows the reader to judge the work taking into consideration two fictional concepts: fiction and the autobiography. The ambivalence derived from this confluence allows us to speak of the ambiguous reading pact, which considers two references (biographical and fictitious) at the same time (Alberca, 2005). The aim of this work is to point out the need to break with such indeterminacy that requires the separation between the two pacts of reading: if the readers looks at the autobiographical, the result will be different if one considers only the fictional aspect. In the following lines, this proposal will be exemplified from the first novel by the Argentine writer Leopoldo Marechal, Adán Buenosayres (1948), in order to determine what consequences this reading suggestion has for the work analyzed here